2019
DOI: 10.1371/journal.pone.0210490
|View full text |Cite
|
Sign up to set email alerts
|

Asthma under control is inversely related with erosive esophagitis among healthy adults

Abstract: BackgroundSome recent studies suggested that reflux esophagitis is positively correlated with asthma. However, there are debates on this issue. The aim of this study is to clarify the true association between reflux esophagitis and asthma in a large population.MethodsMedical records of subjects who received health surveillance checkup between January 2005 and December 2011 were reviewed. Their endoscopic findings, medical history, body mass index, and smoking history were analyzed. Erosive esophagitis was defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Of these, 58 studies have observed male subjects having a higher asthma susceptibility as compared with that of the female subjects significantly [ 16 , 18 , 22 , 37 , 38 , 40 , 47 , 56 , 58 , 62 , 67 , 70 , 71 , 73 , 74 , 79 , 82 84 , 86 , 87 , 92 , 95 , 97 , 99 , 104 , 105 , 107 , 116 , 118 , 120 , 122 , 124 127 , 130 , 131 , 135 , 136 , 139 , 142 , 159 , 170 , 179 , 184 194 , 197 – 200 ]. By contrast, 15 studies showed females having higher asthma risk than males significantly [ 19 , 21 , 33 , 35 , 42 , 49 , 85 , 93 , 110 , 133 , 137 , 195 , 196 , 201 ]. Of these 75 studies, we removed 2 studies [ 125 , 126 ] from the subsequent meta-analysis due to their missing information in risk factor definition and inconsistency in disease definition.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Of these, 58 studies have observed male subjects having a higher asthma susceptibility as compared with that of the female subjects significantly [ 16 , 18 , 22 , 37 , 38 , 40 , 47 , 56 , 58 , 62 , 67 , 70 , 71 , 73 , 74 , 79 , 82 84 , 86 , 87 , 92 , 95 , 97 , 99 , 104 , 105 , 107 , 116 , 118 , 120 , 122 , 124 127 , 130 , 131 , 135 , 136 , 139 , 142 , 159 , 170 , 179 , 184 194 , 197 – 200 ]. By contrast, 15 studies showed females having higher asthma risk than males significantly [ 19 , 21 , 33 , 35 , 42 , 49 , 85 , 93 , 110 , 133 , 137 , 195 , 196 , 201 ]. Of these 75 studies, we removed 2 studies [ 125 , 126 ] from the subsequent meta-analysis due to their missing information in risk factor definition and inconsistency in disease definition.…”
Section: Resultsmentioning
confidence: 98%
“…The association between gender and asthma was reported in 75 studies [ 16 , 18 , 19 , 21 , 22 , 33 , 35 , 37 , 38 , 40 , 42 , 43 , 47 , 49 , 56 , 58 , 62 , 67 , 70 , 71 , 73 , 74 , 79 , 82 87 , 92 , 93 , 95 , 97 , 99 , 104 , 105 , 107 , 110 , 116 , 118 , 120 , 122 , 124 127 , 130 , 131 , 133 , 135 137 , 139 , 142 , 159 , 170 , 179 , 184 201 ]. Of these, 58 studies have observed male subjects having a higher asthma susceptibility as compared with that of the female subjects significantly [ 16 , 18 , 22 , 37 , 38 , 40 , 47 , 56 , 58 , 62 , 67 , 70 , 71 , 73 , 74 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations